SPACE VARIABILITY OF PHENOLOGICAL INDICATORS OF COMMON BEAN CROP - Oliveira, Job Teixeira de; Passos e Carvalho, Morel de [UNESP]; Roque, Cassiano Garcia; Rojo Baio, Fabio Henrique; Kamimura, Karina Marie; Ribeiro, Isabela da Silva; Teodoro, Paulo Eduardo (Univ Federal Uberlandia, 2018)
Common bean (Phaseolus vulgaris L.) has a representative agricultural holding, not only for the economic value of its production, but also for the large area of growing in Brazil. In the harvest 2016/17, this work was conducted in a Quartzarenic Neosol in the municipality of Cassilandia, MS. The objective of this work was to characterize the structure and magnitude of the spatial distribution of phenological indices of the common bean crop and to map the phenological indices in order to visualize the spatial distribution and to evaluate the spatial correlation among common bean yield and plant variables: grain yield (YIE), mass of one hundred grains (MHG), number of grains per plant (NG), number of grains per pod (NGP), number of pods per plant (NP), dry matter (DM), plant length (PL) and stem diameter (SD), sampled in a grid of 117 georeferenced points (81 points of base grid and 36 points of higher density grid). Analysis of these data through statistical and geostatistical techniques made it possible to verify that the production and yield components presented spatial dependence. There was a positive spatial correlation among common bean yield and the mass of one hundred grains, number of grains per pod and plant length, demonstrating that they have a strong spatial dependence.
Keywords: Phaseolus vulgaris L.; Precision agriculture; Geostatistics; Attribute